Analisis Nilai Sosial Dalam Buku “Cerita Rakyat Nias” Karya Sadieli Telaumbanua dan Berliana Siagawati Waruwu - Dewi Murni Hartati Nazara; Noveri Amal Jaya Harefa (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Literature is a form of creative and productive human expression in the form of experiences, thoughts, feelings in producing a work or idea and the spirit has aesthetic value and is able to reflect forms of social reality for society. Literary works are created to convey certain messages that have deep meaning, and their existence cannot be separated from socio-cultural problems in everyday life. The problem in this study is the meaning and value contained in the book